STRESS OF THE NURSE THAT WORKS IN HOSPITALIZATION UNIT. - Henrique Simonetti, Sérgio; Ferraz Bianchi, Estela Regina (Journal of Nursing UFPE / Revista de Enfermagem UFPE, 2016)
Objective: to analyze the stress in the unity of nursing work in hospital and relate to the perception of stress. Method: a descriptive, cross-sectional study with a quantitative approach, with 141 nurses working in public hospitals inpatient units. For data analysis, we used the Statistical Package for the Social Sciences Program SPSS - version 16.0. Results: 92.1% female; 31.2% 41-50 years; 92.2% assistance; 36.2% more than 16 years of training time; 79.4% enrolled in graduate school. As for the stress levels, the nurses had a score of 5.49, considered medium to high level of stress and involved in the fields; interpersonal relations, coordination of activities of the unit and working conditions for the exercise of their profession. The more stressed nurses were the ones that showed low average value at work and it was statistically significant (p <0.05). Conclusion: nurses working in inpatient unit had an average stress level.